Avifauna registrada em estudos de impactos ambientais de usinas hidrelétricas no Brasil - Crispim da Silva, Larissa (Universidade Federal de São Carlos, 2021)
Fauna inventories can be useful tools to reveal a “draw” of biodiversity, helping to monitor and analyze possible changes in an ecosystem. This study aims (1) to compile bird checklists found in the documents of Environmental Impact Study (EIA) and/or the Environmental Plan for the Conservation and Use of the Surroundings of Artificial Reservoirs (PACUERA) of hydroelectric and small hydroelectric plants in Brazil, and (2) to analyze the ecological characteristics of bird species cited in these documents. To date, few studies analyze EIA fauna inventories, suggesting a gap in the knowledge on the potential environmental impacts of these projects. Data were collected from IBAMA's official website (http://licenciamento.ibama.gov.br/), followed by an analysis of the digital files in the categories of pre-defined projects. The analysis was performed on 41 EIAs/PACUERAs present in four biomes. We found 1,493 species, corresponding to 75.71% of the total known Brazilian bird species, includind148 endemic, 77 globally threatened by extinction (BirdLife International and/or IUCN) and 63 nationally threatened (ICMBio). Environmental sensitivity levels could be assigned for 940 species, with 225 (27,1%) considered as having high-, 418 (44,5%) as medium and 267 (28.4%) as low environmental sensitivity. Brazilian policy is proposing more flexible legislation on environmental licensing, which can compromise the quality of these processes and put the protection of biodiversity at risk. For example, reducing the sampling effort for the fauna inventory may question the veracity of these data. Considering the paucity of scientific studies analyzing the environmental diagnosis produced in EIAs, we propose that in future researches, the ecological characteristics of birds be analyzed to understand not only the distribution but also possible impacts not mentioned in those documents.
Bird fauna recorded in environmental impact studies fort hydroelectric plants in Brazil
Keywords: Licenciamento Ambiental; Risco de extinçãp; aves; Sustentabilidade ambiental; Avaliação de impactos ambientais; CIENCIAS BIOLOGICAS::ECOLOGIA